Analisis Pengujian Nilai Kalor Limbah Padat Kelapa Sawit pada PT.Syaukath Sejahtera untuk Bahan Bakar Boiler - Ibrahim Ibrahim; Darwin Harun; Muammar Saputra (Jurnal Teknik Mesin Unsyiah, 2015)
Palm oil processing insdustries does not only produce palm oil but also produce palm waste. The palm waste is filth of palm processing result which is mostly used for fertilizer only and a few of it is used for fuel. The use of palm solid waste, which is not maximal, let the existing energy potency is wasted uselesly. The objective of this research is to calculate the calor value contained in the palm solid waste to be used asfuel of the boiler in palm industries and other industries. The experiment is conducted by burning the palm solid wasteby using calorimeter bomb in 8 mixing ratios. Each mixing ratio is tested 3 times to get the average calor. From the experiment result, it is obtained that the average calor values are: 100% shell = 23.529,47kj/kg,  100% fiber = 20.588,26 kj/kg, 100% empty bunch =18.382,39 kj/kg, 20% shell, 80% fiber= 21.568,67 kj/kg, 0% shell,  60%fiber, 40% empty bunch = 19.117,69 kj/kg, 10% shell, 60% fiber, 30% empty bunch = 19.607,89 kj/kg, 10% shell, 30% fiber, 60% empty bunch = 18.627 kj/kg, 20% shell, 40% fiber, 40% empty bunch = 20.098,08 kj/kg. Thus, the highest calor value is in the burning of 100% of shell and the lowest is in the burning of 100% of empty bunch.